2019
DOI: 10.1021/acsnano.9b04771
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Elastic Liquid-Infused Material for On-Demand Underwater Manipulation of Air Bubbles

Abstract: Precise and robust manipulation of air bubbles will favor intense demands from governing processes of chemical reactions to enhancing transportation efficiency in multiphase engineering systems. Inspired by the working mechanism of mucous lining in lung alveoli, the elastic liquid-infused material (eLIM) is constructed by infiltrating an interconnected porous elastomer with a low-surface-energy lining liquid. With the help of the lining liquid, the pore pressure of the interconnected channels in eLIM can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
(45 reference statements)
1
24
0
1
Order By: Relevance
“…Bubble manipulation using an open surface promotes its superiority in mass/energy exchange as it benefits a direct and sufficient interaction between gas and the aqueous solution. [ 4 ] Thus, a number of research groups were devoted to designing specific surfaces with specific controllability of bubbles, e.g., superhydrophobic cone, [ 5 ] superaerophilic geometry‐gradient channel, [ 6 ] lubricant‐infused slippery surface, [ 7 ] elastic liquid‐infused material, [ 8 ] Janus mesh, [ 9 ] etc. Previous studies, to some extent, have realized spontaneous and directional bubble transport underwater, including 1D bubble transport along channels with the assistance of wettability gradient derived from a Janus interconnected structure, [ 9,10 ] 2D transport depending on specific inclined planes with the aid of buoyancy or on specific asymmetric surfaces with geometric gradient, [ 11 ] demonstrating meaningful but limited bubble transport processes.…”
Section: Figurementioning
confidence: 99%
“…Bubble manipulation using an open surface promotes its superiority in mass/energy exchange as it benefits a direct and sufficient interaction between gas and the aqueous solution. [ 4 ] Thus, a number of research groups were devoted to designing specific surfaces with specific controllability of bubbles, e.g., superhydrophobic cone, [ 5 ] superaerophilic geometry‐gradient channel, [ 6 ] lubricant‐infused slippery surface, [ 7 ] elastic liquid‐infused material, [ 8 ] Janus mesh, [ 9 ] etc. Previous studies, to some extent, have realized spontaneous and directional bubble transport underwater, including 1D bubble transport along channels with the assistance of wettability gradient derived from a Janus interconnected structure, [ 9,10 ] 2D transport depending on specific inclined planes with the aid of buoyancy or on specific asymmetric surfaces with geometric gradient, [ 11 ] demonstrating meaningful but limited bubble transport processes.…”
Section: Figurementioning
confidence: 99%
“…(c) Bio-inspired porous membrane system of a molecule-filtrating glomerulus inspired by the glomerulus and natural sponge [8] . (d) Illustration for the fabrication procedure of bio-inspired PVA/PAN composite porous membrane for hemodialysis [24,54,56] . 例如, 本课题 组 [53] 采用激光刻蚀技术制备了弹性有机高分子多孔 膜, 再将功能液注入到该膜的孔道中, 获得一种在恒压 自动打开, 进行物质交换(图5(a)) [58] .…”
Section: 肾脏是动物体的重要器官之一 其主要功能是调 节动物体内的水、无机盐离子及酸碱平衡 从血液中mentioning
confidence: 99%
“…(c) Dynamic gas and liquid transport process of liquid gating elastomeric porous membrane [53] . (d) Cross section and on-demand bubble manipulation process of bio-inspired elastic liquid-infused membrane [54] 2021 年 4 月 第 66 卷 第 10 期 信使分子NO通过膜孔时, 与膜孔内的铁卟啉结合时, 促使膜的孔道打开, 钾离子能快速通过膜的孔道. 当停 止NO刺激改为太阳光照射时, NO从亚硝酰基铁卟啉 中解离, 膜孔道重新关闭, 此时钾离子不能穿过膜孔.…”
Section: 当前受气孔启发的智能响应仿生多孔膜的构建思 路主要是将具有光或热刺激响应性的聚合物或分子引unclassified
“…[20] In addition to water and oil, studies about responsive wetting performances of gas bubble in water have also aroused much attention. [21] Recently, Wu et al realized in situ regulation from superaerophilicity to superaerophobicity on titanium surfaces by controlling solution surface tension through adding a certain amount of alcohol to the water; [22] Zhang et al reported a liquid-infused porous elastomer, on which the bubble wettability can be reversibly controlled through regulating the mechanical stretching; [23] Jiao et al fabricated TiO 2 square micropillar arrays on titanium sheets and displayed switchable bubble wettability by alternately heating in a dark environment and ultraviolet irradiation in alcohol; [24] Jiang et al presented a multilevel polymeric substrate that can turn from aerophilicity to aerophobicity under heating. [25] In addition, through alternately prewetting and drying treatment was also exhibited on some other surfaces to switch bubble wettability, such as copper mesh, [26] alloy, [27] titanium, [28] stainless, [29] etc.…”
Section: Introductionmentioning
confidence: 99%